The relationship between knowledge management practices and staff performance in Pejabat Setiausaha Kerajaan Negeri Sembilan (SUKNS) / Intan Nurdiani Nordin - Nordin, Intan Nurdiani (2017)
The purpose of this thesis is to identify the relationship between knowledge management practices and staff performance in Pejabat Setiausaha Kerajaan Negeri Sembilan (SUKNS). The knowledge management practices including knowledge acquisition, knowledge dissemination and knowledge utilization. As for the scope of the reports, the reseacher focus on the staff in SUKNS. A questionnaire was used as the main instrument for the data collection. A total of 116 respondents answered the questionnaires which represented 80% of response rate. It was found that knowledge management practices namely knowledge acquisition, knowledge dissemination and knowledge utilization had significant positive and strong relationship with staff performance. Thus, in order to achieve improvement in staff performance, SUKNS has to ensure that the knowledge management practices were applied wisely. Besides, it also found that the most applied practices in SUKNS was knowledge dissemination compared with knowledge acquisition and knowledge utilization. There is also significant difference in staff performance between male and female that might due to different gendered practices. The reseacher have purposed a few recommendation for the improvement of the staff and SUKNS. One of the recommendation, the staff should be exposed into more detailed about knowledge management practices. Even though, knowledge dissemination was well applied in SUKNS, the staff also should apply the other two knowledge management practices. As for the future research, several recommendation were also made in order to improve the research on relationship between knowledge management practices and staff performance. In order to ensure whether knowledge management practices contribute to staff performance, the study should be conducted in a different organization